Structural health monitoring technologies and next-generation smart composite structures - Epaarachchi, Jayantha Ananda; Kahandawa, Gayan Chanaka (Composite materials (CRC Press), 2016)
This book provides valuable insight into cutting-edge advances in structural health monitoring (SHM), smart materials, and smart structures. Comprised of chapters authored by leading researchers, the text showcases exciting developments in general embedded sensor technologies, general sensor technologies, sensor response interrogation and data communication, damage matrix formulation, damage mechanics and analysis, smart materials and structures, and SHM in aerospace applications. Each chapter makes a significant contribution to structural failure prevention, describing methods that increase safety and reduce maintenance costs in a variety of SHM applications.